PENGENALAN POLA PLAT NOMOR KENDARAAN MENGGUNAKAN JARINGAN SYARAF TIRUAN BACKPROPAGATION - David David (SISFOTENIKA, 2013)
Abstract: The application design of license plate pattern recognition using the Backpropagation neural network is the application of license plate recognition done by changing the license plate in form of a photo into a numerical text. This application was made in order to examine whether the method of Backpropagation can recognize the character pattern properly or not. The software process model of license plate recognition study uses the Backpropagation neural network through the prototype approach. The result of this design is the software of license plate pattern recognition using Backpropagation neural network that can commonly recognize the license plate. This application can only recognize license plate image approximately in a one meter distance between a camera and the license plate and does not have light refraction. The result of examination is the success rate of pattern recognition depends on the quality of image, the form of license plate and its writing, light refraction, the distance between a car and the camera, and the determination of temporary character. Keywords: Character Recognition, Backpropagation, Image Processing, License Plate, Smearing Algorithm, Computer Vision.